MaizeDIG: Maize Database of Images and Genomes - Cho, Kyoung Tak; Portwood, John L.; Gardiner, Jack M.; Harper, Lisa C.; Lawrence-Dill, Carolyn J.; Friedberg, Iddo; Andorf, Carson M. (Frontiers in Plant Science, 2019)
Background: An organism can be described by its observable features (phenotypes) and the genes and genomic information (genotypes) that cause these phenotypes. For many decades, researchers have tried to find relationships between genotypes and phenotypes and great strides have been made. However, improved methods and tools for discovering and visualizing these phenotypic relationships are still needed. The maize genetics and genomics database (MaizeGDB, www.maizegdb.org) provides an array of useful resources for diverse data types including thousands of images related to mutant phenotypes in Zea mays ssp. mays (maize). To integrate mutant phenotype images with genomics information, we implemented and enhanced the web-based software package BioDIG (Biological Database of Images and Genomes). Findings: We developed a genotype-phenotype database for maize called MaizeDIG. MaizeDIG has several enhancements over the original BioDIG package. MaizeDIG which supports multiple reference genome assemblies, is seamlessly integrated with genome browsers to accommodate custom tracks showing tagged mutant phenotypes images in their genomic context, and allows for custom tagging of images to highlight the phenotype. This is accomplished through an updated interface allowing users to create image-to-gene links and is accessible via the image search tool. Conclusions: We have created a user-friendly and extensible web-based resource called MaizeDIG. MaizeDIG is preloaded with 2,396 images that are available on genome browsers for ten different maize reference genomes. Approximately 90 images of classically defined maize genes have been manually annotated. MaizeDIG is available at (http://maizedig.maizegdb.org/). The code is free and open source and can be found at (https://github.com/Maize-Genetics-and-Genomics-Database/maizedig)